ANALISIS KEMAMPUAN JANGKA PENDEK BANK PEMBANGUNAN DAERAH KALIMANTAN TIMUR - Nugraha, Adhi Putra (EKONOMIA, 2016)
Every bank have to maintance the liquidity in accordance with the regulation of Bank Indonesia and have to do business with the precautionary principle.The purpose of this study is for analyzing and knowledge about liquidity ratio of Bank Pembangunan Daerah Kalimantan Timur since 2012 untill 2014. The summary of this problem is what about short-time capability of Bank Pembangunan Daerah Kalimantan Timur since 2012 untill 2014 reviewed with banking liqudity ratio, it has been said liquid by Bank Indonesia regulation number: 15/7/PBI/2013 and regulation number: 6/10/PBI/2004.Main teori of this research is financial management and focus to banking liquidity ratio. And the hypotesis is short-time capability of Bank Pembangunan Daerah Kalimantan Timur since 2012 untill 2014 it can be said liquid by Bank Indonesia regulation number: 15/7/PBI/2013 and regulation number: 6/10/PBI/2004.The analysis tools of this study is Liquidity ratio consisting with Loan to Deposit Ratio (LDR) and Cash RatioBased on the analysis and discussion are known if LDR bank BPD Kaltim in 2012 is 56% then increase in 2013 to 88.37% and 77.99% in 2014. For Cash Ratio bank BPD kaltim in 2012 is 42.11%, then decreased in 2013 to 29.21% and 36.02% in 2014. Based on regulation of Bank Indonesia the calculation of the ratio, Bank Pembanguna Daerah Kalimantan Timur can be said as a liquid bank.Based on research result, recommended for next researchers more can be develop research to detail in presents a financial report and analysis result of that financial report specialy in short-time capability.